A novel approach to bipolar plate design in fuel cells with unique flow field geometries - Sevinc, Huseyin; Hazar, Hanbey (Pergamon-Elsevier Science Ltd, 2025)
This study presents a comprehensive numerical investigation of six flow field configurations in a proton exchange membrane fuel cell (PEMFC), including a conventional triple-serpentine design and five newly proposed geometries. The performance of each model was assessed in terms of temperature and pressure distributions, species transport (H2, O2, and H2O), reaction heat generation, and electrochemical behavior. Results revealed that flow field architecture significantly influenced local electrochemical activity and overall cell efficiency. Among all designs, Model 3 (M3) demonstrated superior performance by achieving the highest current density (1.23 A/cm2) and net power output (12.26 W) at 0.4 V-representing a 2.77 % improvement over the serpentine baseline. This enhancement stems from M3 ' s innovative design, which integrates L-shaped internal obstacles within a serpentine-like layout to intensify reactant mixing, improve lateral transport, and promote uniform utilization across the active area. While the Model 2 (M2) model exhibited the most uniform temperature field, the Model 4 (M4) design achieved the lowest pressure drop (0.23 kPa), reducing parasitic losses by 47.73 %. In contrast, the Model 5 (M5) model, despite recording the highest local heat source intensity, suffered from spatially uneven reactions, which potentially hinder performance. The findings underscore the critical role of internal channel design -particularly flow bifurcation and lateral coupling- in optimizing PEMFC performance. The proposed configurations, especially M3, offer promising pathways for next-generation fuel cell flow field design, promoting enhanced power density with minimal pumping losses.
Keywords: Fuel cell; PEMFC; Flow field design; Reactant distribution; Cell performance